2019
DOI: 10.1016/j.jaip.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) Syndrome Identified in the Electronic Health Record Allergy Module

Abstract: Using free-text search of the EHR allergy module identified a large US DRESS syndrome cohort. DRESS prevalence was 2.18 per 100,000 patients. Both liver and kidney injury were frequent, and vancomycin was the most common drug culprit. DRESS cases were morbid and resource-intensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 33 publications
4
65
0
6
Order By: Relevance
“…We found that cutaneous reactions comprised a majority (56.1%) of all HSRs. Prior studies have similarly found that cutaneous reactions are common; dermatologic ADRs were identified to be the most common type of ADRs that was treated in the emergency department (26.3%) [20]. Except for rash, delayed HSR phenotypes were uncommon, as expected.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…We found that cutaneous reactions comprised a majority (56.1%) of all HSRs. Prior studies have similarly found that cutaneous reactions are common; dermatologic ADRs were identified to be the most common type of ADRs that was treated in the emergency department (26.3%) [20]. Except for rash, delayed HSR phenotypes were uncommon, as expected.…”
Section: Discussionsupporting
confidence: 51%
“…However, our SCAR cases have not been validated to date. Prior SCAR validation using an extensive keyword search on EHR allergy list [20] and diagnostic codes [38] has demonstrated low (13-14%) validation.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, Kim et al [48] showed that although the incidence of hospitalization due to the occurrence of SCARs is < 1/1000 person-year, the in-hospital mortality is around 27%. Further studies confirmed that SCARs frequently led to patients' hospitalization and unfavorable outcomes [49][50][51][52] and that these ADRs were often acute emergencies [53]. However, a reporting bias cannot be ruled out.…”
Section: Overall Resultsmentioning
confidence: 99%
“…A recently published case series proposed that 15–37% of DRESS syndrome may be caused by antibiotics [ 16 ]. In an electronic health record review in the USA, from 1980 to 2016, antibiotics were attributed to DRESS syndrome in 74% of cases (vancomycin [39%], β-lactams [23%], fluoroquinolones [4%], tetracyclines [4%], and sulfonamides [3%]) [ 20 ]. Overall, the severity of the antibiotic-induced DRESS in comparison with other culprits is controversial.…”
Section: Introductionmentioning
confidence: 99%